Issues of Creative Personality Development of Engineer under Conditions of Technological Changes in Industrial Production - Valerii Ivashchenko; Vitaliy Petrenko; Oleksandr Yasev; Ivan Avrakhov (Pedagogical Discourse, 2016)
The issues of creative personality development of engineer related to the deindustrialization of economy as well as the decrease of prestige value of engineer’s effort and insufficient encouragement from the state towards the industrial production priority are shown in the article. It was defined that some issues of higher education should be fundamentally coordinated with advanced development of economy for the national educational standard. Training for Master’s Degree should provide both curricular study and scientific research in the specific centers and development laboratories. As a result, the scientific work should be priority for the appropriate academic degree. Credible assure highly professional training of modern industry professionals can only close, as productive as possible connection between education, science and production, motivated and comprehensively stimulated by government institutionsfruitful interactionbetween educational institutions and businesses. Stable and promising guaranteed training of highly qualified specialists going on in such nationwide and state environment, where inventive directions and creative abilities become a kind of social standards and understood as one of the most important factors of social welfare.At the structure of many educational institutions educational work is directed to development of intelligence, maximum filling pupils and students’ heads with all sorts of knowledge, overlooking problems of concrete opportunitiesfor creative application of obtained knowledge. As a result, a graduate will be intellectually developed, even well competent in hisspecialty, but not necessarily creative.Of course, quality score of creative activity depends on specialist’s intellectual development, his level of knowledge and competence. Intelligence and competence - necessary condition for creativity.Key words: creative personality of engineer, engineer’s effort, national educational standard, higher education issues, Master’s degree training.